The Development Of Phonological Acquisition In Children In The Process Of Language Development - Rizky Ardi Pratama; Lailatul Fitria; Yani Lubis (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2023)
Language acquisition consists of three components, namely phonology, syntax, and semantics. However, these three components are not separate from each other in the process of language acquisition. Language acquisition experts, including traditional phonologists who adhere to a behavioristic approach, believe that children's phonetic changes occur because they are not yet perfect at imitating adult speech. However, according to this classical theory, phonetic changes do not occur in adults. Jakobson applies this theory to the phonemic level, whereas Halle argues that phonetic changes reflect the addition of a process or formula to the phonological system in adult.